Konstruksi Sosial Peran Gender dan Relasi Kuasa dalam Film “Andai Ibu Tidak Menikah dengan Ayah” - Ruruh Salma Arista; Yudha Wirawanda (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
Film as a product of popular culture not only represents social reality but also actively participates in constructing values, norms, and power relations. The film Andai Ibu Tidak Menikah dengan Ayah (2025), directed by Kuntz Agus, portrays family dynamics characterized by the absence of the father figure and the dominance of the mother’s role, thereby opening space for analyzing the social construction of gender roles within a patriarchal culture. This study aims to examine the social construction of gender roles as well as power relations as represented through the film’s narratives and symbols. Employing a qualitative approach with a case study strategy, the research is grounded in Peter L. Berger’s theory of the social construction of reality, encompassing the processes of externalization, objectivation, and internalization. Data were collected through documentation in the form of screenshots and dialogue transcripts and analyzed based on visual and audio signs. The findings reveal that the film represents women’s double burden, the supermom myth, and the weakening of paternal masculinity that nevertheless remains embedded within a framework of symbolic patriarchy. Power relations are depicted through the normalization of the mother’s dominant role in both domestic and emotional spheres. These findings indicate that film functions as a medium for both the reproduction and negotiation of patriarchal ideology in contemporary Indonesian society, with important implications for media literacy and gender awareness.